Recurrent Genital Herpes and Balanoposthitis Candidiasis in Men with Incomplete Circumcision: A Case Report - Qaira Anum; Utama, Redha Cipta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Circumcision can reduce the risk of sexually transmitted diseases (STDs). It may reduce males acquiring HSV-2 by 30% and 68% lower prevalence of balanitis than uncircumcised males. There is no report of incomplete circumcision as a risk for STD infection. Case presentation: A 31-year-old male complained of multiple ulcers that covered a yellowish crust on the penile with a burning sensation since 7 days ago. Initially, it was vesicles that turned into ulcers. One month ago, he complained of moist scales on his preputium that felt itchy and smelly. The patient is married and sexually active. History of intercourse with female sex workers without condoms 2 weeks ago. The patient had incomplete circumcision when he was a child; the preputium is still persistent and seldom cleaned regularly. One year ago, there was a history of vesicles on the penis. Physical examination revealed obesity grade 2. Venereological findings showed a whitish pseudo-membrane on the preputium, glans penis, and ulcers in various sizes covered pseudo-membrane surrounded erythema oedema. Laboratory revealed positive IgG HSV1, IgM, and IgG HSV2. A fungal culture is positive candida. Diagnosis established as recurrent genital herpes, balanoposthitis candidiasis, non-specific genital infection, candidiasis intertrigo. The patient has persistent preputium as the entry of commensal pathogens through abrasions in the mucosa, which causes infection. The patient had complete resolution after being administered oral acyclovir, doxycycline, and topical miconazole. Conclusion: Persistent preputium in incomplete circumcision is a risk for developing candidiasis, balanoposthitis, and recurrent genital herpes.